Analisis Kebutuhan Pengembangan Lembar Kerja Murid Elektronik (E-LKM) Berbasis Problem Based Learning Terintegrasi Sustainable Development Goal (SDG) 15 pada Materi Ekosistem Fase E - Regina Faradika; Zulyusri Zulyusri (LP2M UIN Ambon, 2026)
This study aims to analyze the need for developing learning media. Research subjects were selected using purposive sampling, comprising two biology teachers and 33 students from class X E 6. The study employed descriptive qualitative and quantitative methods within an R&D framework using the 4D model, limited to the